A Critically Ill Patient With Central Nervous System Tuberculosis and Negative Initial Workup - Zubair, Adeel S.; Landreneau, Mark; Witsch, Jens; Fulbright, Robert K.; Huttner, Anita; Sheth, Kevin N.; Hwang, David Y. (Frontiers in Neurology, 2020)
Empiric anti-tuberculous therapy should not be delayed in patients with a strong clinical suspicion for TB. Because confirmatory TB testing may be difficult to obtain, early and empiric treatment, when there is concern for central nervous system TB, may result in improved outcomes for patients. GeneXpert is currently an area of active research, and the test returns diagnostic results within hours, which would make it the preferred test for investigating TB meningitis.